Osteogenic Differentiation of Human Amniotic Fluid Mesenchymal Stem Cells Is Determined by Epigenetic Changes - Monika Glemžaitė; Rūta Navakauskienė (Hindawi Limited, 2016)
Osteogenic differentiation of human amniotic fluid derived mesenchymal stem cells (AF-MSCs) has been widely studied in vitro and in vivo as a potential tool for regenerative medicine and tissue engineering. While most of the studies analyze changes in transcriptional profile during differentiation to date there is not much information regarding epigenetic changes in AF-MSCs during differentiation. The aim of our study was to evaluate epigenetic changes during osteogenic differentiation of AF-MS cells. Isolated AF-MSCs were characterized morphologically and osteogenic differentiation was confirmed by cell staining and determining expression of alkaline phosphatase and osteopontin by RT-qPCR. Variation in gene expression levels of pluripotency markers and specific microRNAs were also evaluated. Analysis of epigenetic changes revealed that levels of chromatin modifying enzymes such as Polycomb repressive complex 2 (PRC2) proteins (EZH2 and SUZ12), DNMT1, HDAC1, and HDAC2 were reduced after osteogenic differentiation of AF-MSCs. We demonstrated that the level of specific histone markers keeping active state of chromatin (H3K4me3, H3K9Ac, and others) increased and markers of repressed state of chromatin (H3K27me3) decreased. Our results show that osteogenic differentiation of AF-MSCs is conducted by various epigenetic alterations resulting in global chromatin remodeling and provide insights for further epigenetic investigations in human AF-MSCs.